2012
DOI: 10.1007/s10457-012-9515-7
|View full text |Cite
|
Sign up to set email alerts
|

Homegarden agroforestry systems: an intermediary for biodiversity conservation in Bangladesh

Abstract: Biodiversity conservation is one of the important ecosystem services that has been negatively impacted by anthropogenic activities. Natural forests (NF) harbor some of the highest species diversity around the world. However, deforestation and degradation have resulted in reduced forest land cover and loss of diversity. Homegarden agroforestry (AF) systems have been proven to be an intermediary for biodiversity conservation. In this study, we evaluate the effectiveness of home garden AF practices to conserve tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 33 publications
(24 reference statements)
2
29
0
Order By: Relevance
“…The negative relationship between tree species richness and large homegardens is in keeping with Kumar (2011) although e.g. Abdoellah et al (2006) and Mendez et al (2001) found low correlation whereas Abebe (2005), Kabir and Webb (2009) and Bardhan et al (2012), found a positive relationship. Our negative relationship between tree species richness and large homegardens is probably a result of specific needs and preferences by the owner along with socio-economic factors.…”
Section: Discussionsupporting
confidence: 51%
“…The negative relationship between tree species richness and large homegardens is in keeping with Kumar (2011) although e.g. Abdoellah et al (2006) and Mendez et al (2001) found low correlation whereas Abebe (2005), Kabir and Webb (2009) and Bardhan et al (2012), found a positive relationship. Our negative relationship between tree species richness and large homegardens is probably a result of specific needs and preferences by the owner along with socio-economic factors.…”
Section: Discussionsupporting
confidence: 51%
“…Edible forest gardens have a long tradition among owners of small farms in the southern hemisphere, so called "homegardens", and have been clearly recognized to have social and ecological benefits in tropical areas on all continents (Landreth and Saito 2014;Pulido et al 2008;Bardhan et al 2012;Matsson et al 2015;Willeman et al 2013). In Europe, these gardens are commonly small-scale systems that contribute to the self-sufficiency of urban or suburban households, with the highest presence in central and eastern Europe (MosqueraLosada et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Various other aspects of home gardening in Bangladesh have been well documented, such as the contribution to biodiversity conservation (e.g. Bardhan et al 2012), gender equality (e.g. Hillenbrand 2010;Patalagsa et al 2015) and socio-economic functions (e.g.…”
Section: Introductionmentioning
confidence: 99%